(3GdeSGFd GdgGOjIs - (3TeS GdOjf LYaQ Hf CMeO Hf YHO GdSdGe GdjeGfi GdRjOis
(3ChdgG (B:s
(3eSCdI , jGTjYI GdgGOi Ydjg GdSdGe , gd jLhR YfOce Cf jaYd Gddg SHMGfg edGjQjOg Ce dGjLhR Pdc ? s
(3BNQgG (B:s
(3hgd jUM Pdc YfO efUa ESJJHYhf EdG GdXf hEf CfJe EdG JNQUhf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeY GdQhVI HVhGMi UfYGA s
Keywords: (3Gdabg GdESdGejs